Stone tools in the Ancient Near East and Egypt : ground stone tools, rock-cut installations and stone vessels from the prehistory to late antiquity /: ground stone tools, rock-cut installations and stone vessels from the prehistory to late antiquity. (2019) - Squitieri, Andrea
No abstract available